AI ENABLEMENT: INTEGRATING AI WITH BUSINESS INTELLIGENCE (BI) - Arthi Rengasamy (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
The integration of Artificial Intelligence with Business Intelligence represents a transformative shift in enterprise data analytics and decision-making processes. This comprehensive exploration delves into the core components, implementation challenges, and emerging trends shaping the AI-BI landscape. The convergence has revolutionized traditional analytics capabilities through enhanced predictive modeling, automated insight generation, and improved decision-making processes across various sectors. Manufacturing companies have achieved significant operational cost reductions through predictive maintenance, while financial institutions have enhanced their fraud detection capabilities. The implementation framework addresses technical challenges through automated data validation pipelines, microservices architecture, and robust security protocols. Organizations have reported substantial improvements in data processing efficiency, system reliability, and user adoption rates. The future trajectory points toward increased automation through AutoML, enhanced edge analytics capabilities, and the evolution of explainable AI systems, promising further innovations in enterprise analytics and decision support systems.